2023
DOI: 10.1038/s41467-023-36879-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-time single-molecule 3D tracking in E. coli based on cross-entropy minimization

Abstract: Reaching sub-millisecond 3D tracking of individual molecules in living cells would enable direct measurements of diffusion-limited macromolecular interactions under physiological conditions. Here, we present a 3D tracking principle that approaches the relevant regime. The method is based on the true excitation point spread function and cross-entropy minimization for position localization of moving fluorescent reporters. Tests on beads moving on a stage reaches 67 nm lateral and 109 nm axial precision with a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…HaloTag covalently binds chloroalkane ligands 26 such as the chloroalkane-activated organic fluorescent Janelia-Fluor (JF) dyes 27 . We have previously confirmed that the TF-Halo fusion is functional in vivo (see Supplementary Note 10B in reference 28 ). We applied our SPT method previously used for HaloTag-labeled ribosomes in live E. coli 29 .…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…HaloTag covalently binds chloroalkane ligands 26 such as the chloroalkane-activated organic fluorescent Janelia-Fluor (JF) dyes 27 . We have previously confirmed that the TF-Halo fusion is functional in vivo (see Supplementary Note 10B in reference 28 ). We applied our SPT method previously used for HaloTag-labeled ribosomes in live E. coli 29 .…”
Section: Resultssupporting
confidence: 58%
“…This result suggests that the cellular level of TF-Halo is lower than that of wt TF when they are expressed from the same position on the chromosome, or, alternatively, that TF-Halo has slightly reduced binding capacity to RNC’s compared to the wt TF. However, since TF-Halo is functional 28 , and since the overall RNC binding dynamics of TF-Halo is highly similar in all three scenarios (Fig. 4b, average bound-state dwell times 130-180 ms, and free-state dwell time 20-40 ms), we believe that our measurements represent the binding kinetics of TF to RNCs well.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…This anticorrelated pattern is thought to be mediated by steric exclusion of these two macromolecules. In contrast, smaller components such as free ribosomal subunits and cytoplasmic proteins can diffuse throughout the nucleoid unimpeded (Amselem et al , 2023; Bakshi et al , 2012; Sanamrad et al , 2014), resulting in homogeneous distribution throughout the cytoplasm. This archetypical macromolecular organization is reproduced every generation.…”
Section: Introductionmentioning
confidence: 99%
“…SMLM has also been used to study molecular diffusion properties and their statetransitions in living cells [6][7][8]. Molecules of interest are labeled with bright dyes and imaged in time-lapse to construct molecular motion trajectories for further analysis.…”
Section: Introductionmentioning
confidence: 99%